Biomedical micro- and nanorobots in disease treatment - Mao, Chun; Wan, Mimi (Wiley-VCH, 2023)
Biomedical Micro- and Nanorobots in Disease Treatment Comprehensive resource covering fundamentals at the micro and nano scales, technical advances in micro- and nanorobots, and their biomedical applications Biomedical Micro- and Nanorobots in Disease Treatment: Design, Preparation, and Applications provides foundational knowledge on the subject in the fields of biomaterials, nanotechnology, and biomedicine, discusses the applications of micro- and nanorobots in the cardiovascular, cancer, ophthalmic, orthopedic, gastrointestinal, and nervous system disease treatment, and addresses their biosafety, autonomous motion behavior, and future development trends. The two highly qualified authors comprehensively and systematically introduces the concept source, definition, classification, autonomous movement behavior, and functionality of the technology, providing readers with new ideas, technologies, and methods for modern biomedical research, while also expanding new disease diagnosis, treatment principles, and possible application modes to paint a complete picture of the potential of the technology. Sample topics covered in Biomedical Micro- and Nanorobots in Disease Treatment: Design, Preparation, and Applications include: Substrate selection between metal, inorganic, organic, natural, and hybrid materials, as well as driving systems based on biological components, external fields, and chemical reactions In vivo tracking technologies, including fluorescence imaging, magnetic resonance imaging (MRI), radionuclide and ultrasonic imaging, and other imaging methods Biosafety of micro- and nanorobot substrate through material composition, micro- and nanoscale influence, ultimate destiny, and genotoxicity Trending behavior mechanisms in magnetotactic, phototactic, and chemotaxis systems, and motion control through speed and direction control modes Study on therapeutic mechanism and application for various physiological diseases Summarizing research progress in the preparation, biosafety, functionality, and therapeutic effects of the technology, Biomedical Micro- and Nanorobots in Disease Treatment: Design, Preparation, and Applications is an important and timely resource for biochemists, materials scientists, medicinal chemists, pharmaceutical chemists, bioengineers, biotechnologists, and the greater biotechnological industry.